Answer:
Step-by-step explanation:
Good Question but i don't know
Answer:
y = -2x^2(x - 3)
Step-by-step explanation:
<em><u>Preliminary Remark</u></em>
If a cubic is tangent to the x axis at 0,0
Then the equation must be related to y = a*x^2(x - h)
<em><u>(3,0)</u></em>
If the cubic goes through the point (3,0), then the equation will become
0 = a*3^2(3 - h)
0 = 9a (3 - h)
0 = 27a - 9ah
from which h = 3
<em><u>From the second point, we get</u></em>
4 = ax^2(x - 3)
4 = a(1)^2(1 - 3)
4 = a(-2)
a = 4 / - 2
a = -2
<em><u>Answer</u></em>
y = -2x^2(x - 3)
Answer:
Do you still need help??
Step-by-step explanation:
Answer:
29.5m
29.5m
29.5m
29.5m
Step-by-step explanation:
5m×5.9m
=29.5m
Answer:
3.4 x 10^4
Step-by-step explanation:
1.6 x 10^4 - 5 x 10^4 = -3.4 x 10^4
5 x 10^4 - 1.6 x 10^4 = 3.4 x 10^4